The rollercoaster of subjective well-being in times of multiple crises: evidence of five waves of bi-annual panel data of FReDA survey - Kriechel, Lisa; Bujard, Martin; Hudde, Ansgar (Social indicators research, 2025)
In times of polycrisis, such as COVID-19, the Russian war against Ukraine, and inflation, fear and uncertainties challenge many people. While the impact of the pandemic on subjective well-being was thoroughly studied, the medium-term effects and impacts of more recent crises are still to be observed. Based on the first five waves of the bi-annual (and once tri-annual) large-scale panel FReDA, we show the trend of life satisfaction over 16 time points between April 2021 and January 2023. In addition, we conduct fixed effects and random effects for five subwaves. Results reveal a mostly increasing level of life satisfaction, with setbacks during times of COVID-19 and the Ukraine war. These setbacks also result from restrictions during the pandemic and a higher consumer price index. In a comparison between groups that differentiate between household incomes, the lowest income tercile is particularly affected by crises. Risk factors are unemployment or a bad financial situation. Having children and being in a committed relationship exhibited protective factors. We further observed that the rise in inflation widens the happiness gap so that single parents are disadvantaged. Our research design proved the high potential of combining a higher-frequency panel with monthly information within a wave. As the first study applying this with FReDA data, it paves the way for future analyses of short-term fluctuation with panel data. Our findings on the discontinuity of life satisfaction in times of polycrisis point out that a monitoring of future trends, vulnerable groups, and policy support is indispensable.
Gesehen am 04.02.2026